Determination of biochemical and physical conditions of plastics denominated as “biodegradable” subjected to anaerobic conditions (2012)
The main objective of the study was to determine the biochemical and physical conditions of two different types of polymeric materials (HDPE with oxo-additive and PLA) when subjected to conditions similar to those presented inside a sanitary landfill. These materials are commercialized within the country claiming to be biodegradable under certain conditions. However, the conditions in which such degradation may occur are completely unknown from those presented inside s solid waste final disposal site (sanitary landfill). The experiment simulated the general conditions to which the materials would be subjected once inside a sanitary landfill, (absence of molecular oxygen, absence of light, constant temperature, high humidity, among others). Changes in biochemical and physical conditions were monitored as well as the container. These changes may indicate degradation of the polymers. Along the experiment, not enough evidence could be observed that doubtlessly showed actual biodegradation in any of the plastic materials tested.